Fumigant Toxicity of Siamese Citrus Fruit Extract (Citrus nobilis) as a Botanical Pesticide in Culex sp. - Devi Syafrianti; Safrida Safrida; Jauharati Nassaf (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2020)
Toxicity is the ability of a substance that is destructive when exposed to organisms. These substances can come from plants to used as plant-based pesticides. Siam orange peel waste (Citrus nobilis) can be used as the main ingredient of botanical pesticides because it contains bioactive compounds. The purpose of this research is to see the ability of the concentration of siam citrus fruit extracts that can cause mosquito death by 50%. This type of research is experimental and a quantitative approach. The experimental design used a Factorial Complete Randomized Design consisting of seven different treatments and three observation times. These treatments were the concentration of 0% conjoined orange peel extract as a negative control, 30%, 45%, 60%, 75%, 90%, and commercial products as a positive control, the treatment was carried out in four replications. Data were analyzed using probit regression analysis. Probit test results obtained that LC50 value is 49.86%, the concentration that can be used is in the treatment of P3 with a concentration of 60% of Siamese orange peel extract. The conclusion of this research proves that the administration of conjoined orange peel extract can cause Culex mosquito mortality by 50% at a concentration of 60%.